Efektifitas Pembelajaran Matematika Realistik Untuk Meningkatkan Kemampuan Mengenal Bangun Ruang Pada Anak Tunagrahita Ringan - Niko Pratama; Irdamurni -; Zulmiyetri - (Universitas Negeri Padang, 2013)
ABSTRACT This research background by the apparent problems in the field, ie, mild mental retardation X-class children in special schools D.I Pearl Budi Lubuk Alung who have difficulty in identifying geometrical. This is evident from the ability of children to recognize initial geometrical children have difficulty on tests give researchers, children may not be able to answer all the test correctly. This study aims utntuk prove effective or not learning mathematics to improve the ability to know the realistic geometrical. Research methodology that researchers use is the single-subject experimental research (SSR) using A-B-A design, in order to see the children's ability to recognize geometrical before given treatment, during treatment delivery and compared with the ability of the child after the treatment is no longer given. Data analysis was conducted in this research is a visual data analysis is illustrated by a graph. The results were analyzed covers the number of observations in the baseline condition I (A1) five sessions, six intervention sessions and baseline II (A2) five meetings. The results of this study looks at the baseline I (A1) the highest ability children is 21.3%, in the intervention (B) the child's ability score is 86% and the baseline II (A2) the child's ability score is 84%. Judging from the data analysis in the conditions and data analysis between conditions showed a change in the ability to know geometrical soft X mental retardation in children towards better learning mathematics through realistic, it can be concluded that learning mathematics through realistic mild mental retardation children in special schools x Pearl Budi Lubuk Alung already be familiar with the five types of geometrical (beam, tubes, cones, blocks and cubes). Therefore, it is suggested that the classroom teacher or math teacher for learning mathematics is used in identifying realistic geometrical mild mental retardation in children. Kata Kunci : Bangun Ruang; Anak Tunagrahita Ringan; Pembelajaran Matematika Realistik